Utilization of Online Learning Media during the Covid-19 Pandemic in Teaching and Learning Activities by Teachers at MTs Muhammadiyah Karangkajen - Nur Fitri Mutmainah; Silvi Lailatul Mahfida (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The Covid-19 pandemic has forced the government to issue regulations for various sectors including the education sector to reduce face-to-face learning activities so that teaching and learning activities were carried out online. Some of the teachers of MTs Karangkajen still have not mastered digital media so that teachers find it difficult to prepare effective media and materials for students. Training for teachers are needed to master the skills of preparing learning materials digitally. The expected impact is that teachers are able to design learning media independently and can be better understood by students. The purpose of this activity is to provide understanding and train teachers to be able to use and implement online learning by optimizing powerpoints and learning videos. The method of activity is observation, socialization and training. A total of 15 teachers participated in the activities held at the school. All participants can access training materials online and actively participate in the training. The results of the activity are in the form of a design of learning materials made by the trainee teachers themselves. It is hoped that the design can be implemented in more effective learning and improve student understanding.